Two new species of the Entoloma quadratum–murrayi complex in Japan - Hirotoshi Sato; Otomi Satomi; Yoriko Sugiyama (PLoS ONE, 2025)
We describe two new species, Entoloma . kermesinum sp. nov. and E . flavescens sp. nov., which are confused with E . quadratum and E . murrayi , respectively. We sequenced the large subunit of mitochondrial ribosomal RNA, the nuclear ribosomal internal transcribed spacer region and 22 single-copy genes for 51 specimens of E . kermesinum , E . flavescens , E . album , and related species. Species boundaries were assessed using the molecular phylogenetics and population genetics approaches. Specimens of E . kermesinum , E . flavescens , and E . album formed independent clades, which were phylogenetically distinct from the specimens of E . quadratum and E . murrayi collected around the type locality (i.e., New England). Although the phylogenetic distance between E . flavescens and E . album was small, gene flow between them was restricted in areas where they coexisted, suggesting reproductive isolation. Therefore, these five species can be treated as independent species. We found characteristics useful for identifying E . kermesinum and E . flavescens . In particular, E . kermesinum is characterized by a crimson to brown-red and fibrillose pileus, finely covered by whitish fibrous scales; E . flavescens is characterized by a lemon-yellow to tan and shiny-to-silky pileus. In addition, relatively large basidiospores and clamp connections are diagnostic features of these two species.